2019
DOI: 10.1016/j.ecoleng.2018.11.026
|View full text |Cite
|
Sign up to set email alerts
|

A constructed wetland for treatment of an impacted waterway and the influence of native waterfowl on its perceived effectiveness

Abstract: A constructed, variable-flow treatment wetland was evaluated for its ability to reduce microbial loads from the Banklick Creek, an impacted recreational waterway in Northern Kentucky. For this study, levels of traditional (Escherichia coli and enterococci measured by culture and molecular techniques) and alternative fecal indicators (infectious somatic and F+ coliphage, Clostridium spp. and Clostridium perfringens by culture), potential pathogens (molecular signal of Campylobacter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The wetland sampling has been described in our previous study [ 11 ]. Briefly, samples were collected from June through September 2017 from five sites in the Banklick Creek Treatment Wetland located in Fort Wright, Kentucky (39°01′14.2″ N 84°31′42.1″ W) ( Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wetland sampling has been described in our previous study [ 11 ]. Briefly, samples were collected from June through September 2017 from five sites in the Banklick Creek Treatment Wetland located in Fort Wright, Kentucky (39°01′14.2″ N 84°31′42.1″ W) ( Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acids were then extracted from the supernatant using the AllPrep DNA/RNA Mini Kit (Qiagen, Germantown, MD, USA), following the manufacturer’s instructions. A Campylobacter genus-specific PCR assay was used to amplify 28 of the samples which were positive via the previous qPCR assay for Campylobacter genera [ 11 , 20 , 28 ] ( Table S1 ). The amplicons were cloned into pCR4.1 TOPO (Invitrogen, Carlsbad, CA, USA) to aid in further identification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no changes in concentration of fecal indicator during the treatment period, and the human marker HF183 concentration was lowered significantly at later stages than that of beginning stage of treatment. Furthermore, at the later stage treatment Campylobacter signals were significantly higher and suggested that relying on general fecal indicator for determination of CWs efficacy is not an ideal condition always (McMinn et al, 2019).…”
Section: Wetlands For Pathogens and Virus Removalmentioning
confidence: 99%
“…Fecal pollution management represents a major challenge for water quality authorities worldwide. Fecal waste can enter waterways from a variety of sources such as leaky sewer lines, faulty septic systems, stormwater run-off, improper agricultural waste management practices, and local wildlife [15]. When fecal pollution is present in surface waters, it can represent a public health risk due to the presence of disease causing pathogens (see [6] for review), as well as lead to severe economic burdens [7].…”
Section: Introductionmentioning
confidence: 99%